Exploring cognitive approach in the teaching of literature for secondary schools in Malaysia - Abdullah, Suhaila; Idrus, Faizah (2020)
This paper discusses cognitive approach and how it could play an important role in the teaching of literature in secondary schools in Malaysia. Cognitive approach brings about cognitive poetics, a theory which studies literary works by using psychology. The rationale for this study is to find out whether secondary school teachers could incorporate cognitive approach particularly cognitive poetics in the teaching of literature conducted in their classrooms. Since a new curriculum, Kurikulum Standard Sekolah Menengah (KSSM) or translated as The Standards-Based Curriculum for Secondary Schools, has been introduced in the Malaysian education system by the Ministry of Education in 2018, English Literature in secondary schools has become an elective course for students who could opt to sit for the English Literature Paper for the Malaysian School Leaving Exam (that is equivalent to O’ Levels Certificate) commencing in 2020. Due to the change of curriculum and past news reports that recorded a decreasing number of students who sat for the paper from 2017 onwards, there is a need to study the teaching approaches used in classrooms and in addition, to identify whether the use of cognitive poetics in teaching literature could assist teachers in teaching this subject in order to facilitate students’ understanding of literary texts. This paper proposes that teachers could draw students’ attention to the psychology of the authors and characters by practising this approach as a teaching strategy instead of focusing solely on main themes or merely applying the study of poetics in literary works. The paper explores whether this approach could serve as a method to support thinking skills in the teaching of literature to secondary school students in Malaysia and whether it could fulfil the goals of attaining HOTS (Higher Order Thinking Skills) as stated in the new KSSM curriculum set by the Ministry of Education, Malaysia.